THE EFFECT OF BRAND IMAGE AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF NATAZA LAUNDRY CUSTOMERS - Purnama Puji; Imas Trimayanti; M. Anissul Fata (PATEMON: Multidisciplinary Research, 2025)
Purpose: Aims to investigate the influence of brand image and service quality on customer satisfaction among customers of Nataza Laundry Pandan Branch, focusing on both partial and simultaneous effects, as well as identifying which variable has the most dominant impact. Research Methodology: A quantitative descriptive method was employed, utilizing a sample of 59 respondents who are customers of Nataza Laundry Pandan Branch. Data were collected through questionnaires. The analysis involved validity and reliability tests, classical assumption tests, multiple linear regression, and determination coefficient tests, alongside partial (t) and simultaneous (F) tests. Results: The findings indicate that both brand image and service quality significantly affect customer satisfaction. The simultaneous test showed Fcal ≥ Ftabel (52.075 ≥ 3.16), confirming a collective influence. For partial effects, brand image (X1) had a coefficient of 0.451, while service quality (X2) had a coefficient of 0.395, both with significance values < 0.05, indicating a positive and significant impact on customer satisfaction. Limitations: The study is limited to the Nataza Laundry Pandan Branch and may not be generalizable to other contexts or locations. The sample size, though adequate for this analysis, may not capture broader customer perspectives. Contribution: This research contributes to understanding the factors influencing customer satisfaction in the laundry service industry, providing insights for businesses to enhance their brand image and service quality.